RR Lyrae Stars as Seen by the Kepler Space Telescope - Plachy, Emese; Szabó, Róbert (Frontiers in Astronomy and Space Sciences, 2021)
The unprecedented photometric precision along with the quasi-continuous sampling provided by the Kepler space telescope revealed new and unpredicted phenomena that reformed and invigorated RR Lyrae star research. The discovery of period doubling and the wealth of low- amplitude modes enlightened the complexity of the pulsation behavior and guided us towards nonlinear and nonradial studies. Searching and providing theoretical explanation for these newly found phenomena became a central question, as well as understanding their connection to the oldest enigma of RR Lyrae stars, the Blazhko effect. We attempt to summarize the highest impact RR Lyrae results based on or inspired by the data of Kepler space telescope both from the nominal and the K2 missions. Beside the three most intriguing topics, the period doubling, the low-amplitude modes, and the Blazhko effect we also discuss the challenges of Kepler photometry that played a crucial role in the results. The secrets of these amazing variables, uncovered by Kepler, keep the theoretical, ground-based and space-based research inspired in the post-Kepler era, since light variation of RR Lyrae stars is still not completely understood.